Group-based delivery of interventions in traumatic brain injury rehabilitation: a scoping review. Issue 20 (24th September 2016) - Patterson, Freyr; Fleming, Jennifer; Doig, Emmah
Abstract: Purpose: Whilst there are potential advantages of group-based interventions in rehabilitation, facilitation of groups for patients following traumatic brain injury (TBI) has challenges due to the complexity of impairments experienced. This paper aims to review the literature concerning therapy groups within TBI rehabilitation. Method: A scoping review with systematic searching of relevant databases and review of reference lists of included studies was conducted. Key search terms included brain injury, group and rehabilitation OR therapy OR intervention. Studies were included if at least some participants had a TBI diagnosis and they investigated rehabilitation interventions conducted in a group setting. Articles were collated, summarised and key findings are presented. Results: The total number of included articles was 99. The results indicated group interventions are widely practised in TBI rehabilitation. Existing research consists mostly of pre–post intervention studies addressing cognitive impairments with outpatient participants. Most studies have identified significant positive changes on some targeted outcome measures suggesting group interventions are effective. Conclusions: Studies of the effectiveness of interventions targeting 'real-world' activities and participation-based goals are under-represented in the TBI rehabilitation literature. Further research investigating the effectiveness of group processes and the perceptions of patients and clinicians is warranted to guide clinical practice. Implications for Rehabilitation: Group-based interventions are common in TBI rehabilitation, usually targeting cognitive skills and impairments. The majority of studies demonstrated positive changes pre–post group interventions on some outcome measures. Few studies directly compare the outcome of an intervention delivered in a group setting to the same intervention delivered in an individual setting. Patients perceive group interventions to be beneficial for sharing experiences and reducing isolation, receiving help and feedback and, assisting with adjustment and adaptation to life after TBI, however, this research is limited. Greater emphasis on group-delivered interventions that target 'real world' activities, or participation may be beneficial with this population. Further research regarding consumer experiences and processes that facilitate effective group interventions in TBI rehabilitation is recommended.